Surface electrocardiography characteristics and radiofrequency catheter ablation of idiopathic ventricular arrhythmias originating from the left infero-septal papillary muscles: differences from those originating from the left posterior fascicle. Issue 6 (24th April 2017) - Li, Shixing; Wang, Zulu; Shan, Zhaoliang; Shi, Xiangmin; Liang, Ming; Liang, Yanchun; Jin, Zhiqing; Han, Yaling; Wang, Yutang
Abstract: Aims: Distinguishing between ventricular arrhythmias originating from the left ventricular infero-septal papillary muscles (PM) and those from the left posterior fascicle (LPF) by surface electrocardiography (ECG) is very difficult. This study aimed to report the ECG characteristics and radiofrequency catheter ablation of PM and LPF ventricular arrhythmias. Methods and results: A total of 127 patients underwent catheter ablation of idiopathic ventricular arrhythmias originating from the LPF ( n  = 106; 85 males; 10–70 years) or PM ( n  = 21; 14 males; 4–68 years) were studied. A three-dimensional electroanatomic system (3D-EAS) was used to aid ablation. PM ventricular arrhythmias had a longer QRS duration (154.4 ± 18.0 vs. 119.7 ± 12.6 ms, P  < 0.001) than LPF ventricular arrhythmias. All 7 ventricular arrhythmias with QRS duration >160 ms originated from the PM, whereas all 87 ventricular arrhythmias with QRS duration <130 ms arose from the LPF. In 33 ventricular arrhythmias with QRS 130–160 ms, all 13 with V i / V t ≤ 0.85 originated from the PM, and 19 of 20 with V i / V t > 0.85 arose from the LPF. Of the 8 PM ventricular arrhythmias patients whose initial ablation was undertaken using a non-irrigated 4 mm-tip catheter, 1 failed and 6 recurred. However, of the remaining 13 ones using an irrigated catheter and the 3D-EAS, all succeeded and 2 recurred. No complications were noted in any patient. Conclusion: PM ventricular arrhythmias could be identified from LPF ventricular arrhythmias by calculation of QRS duration combined with V i / V t using ECG.